Using a life course approach to understand involvement in volunteering in Australia - Reimondos, A; Gray, E; Khoo, S-E (My University, 2011)
This paper is based on Stage 1 of a research project funded by the Department of Families, Housing, Community Services and Indigenous Affairs. Stage 1 focuses on the analysis of HILDA data to examine volunteering over the life course. Stage 2 examines volunteering for different types of organizations using Negotiating the Life Course data.
Keywords: Social Capital; Social Capital -- Volunteering (Sporting clubs, Service Clubs etc); Social engagement; Social Capital; Volunteering (Sporting clubs, Service Clubs etc); Social Engagement